Improving Natural Science Learning Outcomes on Energy and Its Changes Through Paired Practice Methods at MIS NU Ratan Daya - Fitriani, Ety (MANDAILING GLOBAL EDUKASIA, 2024)
The reality in Class III MIS NU Ratan Daya shows that, based on the daily test results, 4 out of 11 students achieved mastery, while 7 students did not. This indicates that the number of students who did not achieve mastery is greater than those who did. Based on the results of the pre-action test and initial observations, the researcher, who is also the class teacher, decided to implement a varied method that would engage students and make learning more exciting. In this case, the researcher used the paired practice method. This research employs the action research model, conducted in Class III MIS NU Ratan Daya. The researcher, who is also the teacher at this school, chose this school as the location for the study. The subjects of the study are the 11 students in Class III MIS NU Ratan Daya. The research was carried out during the beginning of the new school year 2022/2023, specifically from January to March 2023. Data collection techniques in this study include tests, observations, and documentation. The results of the pre-cycle test showed that the students' learning outcomes, in a classical sense, were 36.3%, categorized as